1988
DOI: 10.1111/j.1532-5415.1988.tb02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Drug Practice In Nursing Homes

Abstract: This study examined the administration of psychotropic medication to Medicaid recipients who resided continuously in an Illinois nursing home during 1984. Of these residents, 20,037 (60%) received at least one such medication during the year, with administration most likely for those from the ages of 45 to 74 years. Haloperidol, thioridazine, and flurazepam were the most frequently prescribed drugs of those examined. The study also investigated the relationship of demographic and institutional variables to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
2
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 10 publications
11
64
2
2
Order By: Relevance
“…This is in agreement with studies 3,5 examining the prevalence of the use of psychotropics among nursing home residents. These studies have reported rates ranging from 27% to 60%, which are higher than the rates of 9.3 to 30.6% found in community studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in agreement with studies 3,5 examining the prevalence of the use of psychotropics among nursing home residents. These studies have reported rates ranging from 27% to 60%, which are higher than the rates of 9.3 to 30.6% found in community studies.…”
Section: Discussionsupporting
confidence: 81%
“…3,4 Although psychotropics are one of the classes of medications most prescribed in nursing homes for the elderly, studies examining their prescribing patterns are limited in both number and scope. These studies have reported a wide range of prevalence of psychotropic prescription (10-60%) and have mainly focused on the classes of psychotropics and prevalence of psychiatric morbidity among residents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gilleard et al (1983) surveyed residents of Local Authority homes and elderly patients in hospitals and psychogeriatric wards in a London borough; overall, 13% were taking neuroleptics. Buck (1988) studied medication rates among Medicaid recipients in the state of Illinois. Sixty per cent of this population received at least one psychotropic drug.…”
Section: Non-developmentally Disabled Peoplementioning
confidence: 99%
“…However, use of antipsychotics in older people with dementia can be associated with significant problems, including fractured neck of femur as a result of falls, impaired cognitive functioning and an adverse prognosis (Bouman & Pinner, 2000). Despite these concerns, a number of studies have found excessive use of antipsychotics in nursing home residents (Jenks & Clauser, 1991;Buck, 1998). Experience from the USA has shown that following the introduction of clear guidance supported by legislation, the prescription of such drugs for residents of nursing homes can be reduced by up to 41% (Shorr et al, 1994).…”
Section: Discussionmentioning
confidence: 99%